Catalytic farming: reaction rotation extends catalyst performance. Issue 5 (26th November 2018) - Elhage, Ayda; Lanterna, Anabel E.; Scaiano, Juan C.
Abstract : Catalytic farming, through reaction rotation, can reactivate the catalyst increasing longevity and product yield. Abstract : The use of heterogeneous catalysis has key advantages compared to its homogeneous counterpart, such as easy catalyst separation and reusability. However, one of the main challenges is to ensure good performance after the first catalytic cycles. Active catalytic species can be inactivated during the catalytic process leading to reduced catalytic efficiency, and with that loss of the advantages of heterogeneous catalysis. Here we present an innovative approach in order to extend the catalyst lifetime based on the crop rotation system used in agriculture. The catalyst of choice to illustrate this strategy, Pd@TiO2, is used in alternating different catalytic reactions, which reactivate the catalyst surface, thus extending the reusability of the material, and preserving its selectivity and efficiency. As a proof of concept, different organic reactions were selected and catalyzed by the same catalytic material during target molecule rotation.